Safety, pharmacokinetic, pharmacodynamic and clinical activity of molibresib for the treatment of nuclear protein of the testis carcinoma and other cancers: Results of a Phase I/II open‐label, dose escalation study. Issue 6 (26th November 2021) - Cousin, Sophie; Blay, Jean‐Yves; Garcia, Irene Braña; de Bono, Johann S.; Le Tourneau, Christophe; Moreno, Victor; Trigo, Jose; Hann, Christine L.; Azad, Arun A.; Im, Seock‐Ah; Cassier, Philippe A.; French, Christopher A.; et al.
Abstract: Molibresib is an orally bioavailable, selective, small molecule BET protein inhibitor. Results from a first time in human study in solid tumors resulted in the selection of a 75 mg once daily dose of the besylate formulation of molibresib as the recommended Phase 2 dose (RP2D). Here we present the results of Part 2 of our study, investigating safety, pharmacokinetics, pharmacodynamics and clinical activity of molibresib at the RP2D for nuclear protein in testis carcinoma (NC), small cell lung cancer, castration‐resistant prostate cancer (CRPC), triple‐negative breast cancer, estrogen receptor‐positive breast cancer and gastrointestinal stromal tumor. The primary safety endpoints were incidence of adverse events (AEs) and serious AEs; the primary efficacy endpoint was overall response rate. Secondary endpoints included plasma concentrations and gene set enrichment analysis (GSEA). Molibresib 75 mg once daily demonstrated no unexpected toxicities. The most common treatment‐related AEs (any grade) were thrombocytopenia (64%), nausea (43%) and decreased appetite (37%); 83% of patients required dose interruptions and 29% required dose reductions due to AEs. Antitumor activity was observed in NC and CRPC (one confirmed partial response each, with observed reductions in tumor size), although predefined clinically meaningful response rates were not met for any tumor type. Total active moiety median plasma concentrations after single and repeated administration were similar across tumor cohorts. GSEA revealed that gene expression changes with molibresib varied by patient, response status and tumor type. Investigations into combinatorial approaches that use BET inhibition to eliminate resistance to other targeted therapies are warranted. Abstract : What's new? Molibresib is a BET inhibitor currently being tested against various solid tumors. Part 1 of this study, published previously, established a recommended dosage in patients with nuclear protein in testis carcinoma. Here, the authors present part 2, reporting on the safety and efficacy of molibresib in a wider array of tumor types. While they found no unexpected toxicities, adverse events caused 83% of patients to pause treatment, and 29% to lower their dosage. Molibresib showed some anti‐tumor activity, although clinically meaningful response rates were not observed by the end of the trial.